The Expression of TRIM6 Activates the mTORC1 Pathway by Regulating the Ubiquitination of TSC1-TSC2 to Promote Renal Fibrosis - Liu, Weiwei; Yi, Yang; Zhang, Chuanfu; Zhou, Baojuan; Liao, Lin; Liu, Wenrui; Hu, Jing; Xu, Qiming; Chen, Jie; Lu, Jianrao (Frontiers in Cell and Developmental Biology, 2021)
Renal fibrosis is considered as the final pathway of all types of kidney diseases, which can lead to the progressive loss of kidney functions and eventually renal failure. The mechanisms behind are diversified, in which the mammalian target of rapamycin (mTOR) pathway is the most important regulation that accounts for the disease. Several processes that are regulated by the mTOR pathway, such as autophagy, epithelial-mesenchymal transition (EMT), and endoplasmic reticulum (ER) stress, are tightly associated with renal fibrosis. In this study, we have reported that the expression of tripartite motif-containing (TRIM) protein 6, a member of TRIM family protein, was highly expressed in renal fibrosis patients and positively correlated with the severity of renal fibrosis. In out established in vitro and in vivo renal fibrosis models, its expression was upregulated by the Angiotensin II-induced nuclear translocation of nuclear factor-κB (NF-κB) p50 and p65. In HK2 cells, the expression of TRIM6 promoted the ubiquitination of tuberous sclerosis proteins (TSC) 1 and 2, two negative regulators of the mTORC1 pathway. Moreover, the knockdown of TRIM6 was found efficient for alleviating renal fibrosis and inhibiting the downstream processes of EMT and ER in both HK2 cells and 5/6-nephrectomized rats. Clinically, the level of TRIM6, TSC1/2, and NF-B p50 was found closely related to renal fibrosis. As a result, we have presented the first study on the role of TRIM6 in the mTORC1 pathway in renal fibrosis models and provided a potential treatment of renal fibrosis using TRIM6-specific shRNAs.